Mathematical operation and symbol notation
 Statements
H < J,
F < H,
I ≤ J = K
Conclusions
I. H > I
II. I ≥ F

 if only Conclusion I follows
 if only Conclusion II follows
 if either Conclusion I or II follows
 if neither Conclusion I nor II follows
 if both Conclusions I and II follow

View Hint View Answer Discuss in Forum
Given that,
H < J .....(i)
F < H .....(ii)
I ≤ J = K ......(iii)
On combining the statement (i), (ii) and (iii), we get
F < H < J = K ≥ I
Conclusions
I. H > I (false)
II. I ≥ F (false)Correct Option: D
Given that,
H < J ..............(i)
F < H ..............(ii)
I ≤ J = K ......(iii)
On combining the statement (i), (ii) and (iii), we get
F < H < J = K ≥ I
Conclusions
I. H > I (false)
II. I ≥ F(false)
So, it is clear that neither Conclusion i nor II follows the given statements.
 Statements
A < B < C ≤ D = E
Conclusions
I. B ≤ E
II. B < E

 if only Conclusion I follows
 if only Conclusion II follows
 if either Conclusion I or II follows
 if neither Conclusion I nor II follows
 if both Conclusions I and II follow

View Hint View Answer Discuss in Forum
Given that,
A < B < C ≤ D = E
Here, statements are already combined.
Conclusions
I. B ≤ E (false)
II. B < E (true)Correct Option: E
Given that,
A < B < C ≤ D = E
Here, statements are already combined.
Conclusions
I. B ≤ E (false)
II. B < E (true)
So, it is clear that only Conclusion II follow from the given statements.
 Statements
P > M > Q,
Q > Z > N
Conclusions
I. M ≥ Z
II. N < P

 if only Conclusion I follows
 if only Conclusion II follows
 if either Conclusion I or II follows
 if neither Conclusion I nor II follows
 if both Conclusions I and II follow

View Hint View Answer Discuss in Forum
Given that,
i. P > M > Q
ii. Q > Z > N
On combining the statement (i) and (ii) we get
P > M > Q > Z > N
Conclusions
I. M ≥ Z (false)
II. N < P (true)Correct Option: B
Given that,
i. P > M > Q
ii. Q > Z > N
On combining the statement (i) and (ii) we get
P > M > Q > Z > N
Conclusions
I. M ≥ Z (false)
II. N < P (true)
So, it is clear that only Conclusion II follows from the given statements.
 Which of the following expression will be true, if the given expression K ≥ G > H ≤ F is definitely true ?

 F ≥ K
 H < K
 F < G
 K ≥ H
 None of thease

View Hint View Answer Discuss in Forum
Now, we can check all the options one by one
(a) F ≥ K
Given equation,
1. K ? G > H ? F
Then relation between F and K will be from 1,
2. K ? H ? F (cannot decide between K and F)
(b) H < K
from 1. Relation between H and K will be
3. K ? G > H
from 3
H < K
(c) F < G
Relation between F and G from 1,
G > H ? F (cannot decide between G and F)
(d) K ≥ H
Relation Between K and H,
From 1. K ? G > H means K > HCorrect Option: B
Now, we can check all the options one by one
(a) F ≥ K......(false)
(b) H < K .......(true)
(c) F < G ......(false)
(d) K ≥ H ......(false)
So, it clear that option (b) true ,
 In which of the following expression will the expression ' A < D' be definitely true ?

 A ≥ B = C < D
 A > B = C ≥ D
 A < B = C ≤ D
 A > B < C ≤ D
 None of the above

View Hint View Answer Discuss in Forum
Try all option one by one.
Correct Option: C
Try all option one by one.
From the expression "C "
A < B = C ≤ D,
A < D will be definitely true .